Predição da energia metabolizável do milho de primeira e segunda safra para leitões - Esteves, Lucas Antonio Costa; de Oliveira, Newton Tavares Escocard; Huepa, Laura Marcela Diaz; Ferreira, Silvia Letícia [UNESP]; Castilha, Leandro Dalcin; Pozza, Paulo Cesar (FapUNIFESP (SciELO), 2017)
Corn is one of the primary ingredients in swine diets, but there is a variation in its chemical composition and metabolizable energy (ME) content. Therefore, faster methods are required that can determine more accurate ME values to improve piglet diets. This study determined and predicted the ME of corn from first and second harvests for piglets. Two experiments were conducted to determine the ME values for 18 corn batches, evaluating corn from first and second harvests. The corn batches were analysed to determine the concentration of dry matter (DM), starch (ST), neutral detergent fiber (NDF), acid detergent fiber (ADF), crude protein (CP), ether extract (EE), ash, calcium (Ca), phosphorus (P) and gross energy (GE). To determine the ME values, 40 piglets were used in each experiment, grouped into a randomized block design with four replicates. The ME of the corn from the first and second crops ranged from 3281 to 3509 and from 3143 to 3652 kcal/kg on an as-fed basis, respectively, and the fitted equations to predict the ME presented a low R2. The best fit equation for predicting the ME of corn for piglets was determined to be ME= - 6306.15 + 400.652ADF + 117.286ST + 24924.7Ca + 2489.66P – 148.41CP (R2=0.44) for the first harvest; ME= -7560.08 + 2.66895GE – 120.69ADF (R2=0.48) for the second harvest; and ME= 2848.95 + 68.5714NDF + 161.938EE – 5563.5Ca – 1454.2P (R2=0.41) for the joint harvest.
Predicting the metabolizable energy of first and second corn harvests for piglets
Keywords: Metabolizability coefficients; Prediction equations; Swine